Digital Topographical Bibliography : of Ancient Egyptian Hieroglyphic Texts, Statues, Reliefs, and Paintings - The Griffith Institute; University of Oxford (2014)
[Engl.:] "The Griffith Institute, University of Oxford, launches the new 'Digital Topographical Bibliography'. Alongside searchable PDFs of the current print version, vols. 1-7, the new website presents the digital framework of the project and samples of new data focusing on three case-studies, namely Tuna el-Gebel, Tell el-Far'un (both formerly in PM IV) and royal statues of provenance not known (formerly in PM VIII, Part 1)."